Genetic analysis of the Saraiki population living in Pakistan. Issue 3 (2nd July 2016) - A, Jilani; A, Nadeem; M A, Tahir; N, Rasool
ABSTRACT: Autosomal short tandem repeat (STR) markers are a powerful tool used in forensic sciences for profile matching and paternity testing, sibship and kinship analysis. This study represents the allele frequency distribution of 15 autosomal STR multiplex of the Saraiki population living in Pakistan. Allele frequencies of this population were compared with the other populations living in Pakistan. Buccal swabs were taken from 150 unrelated individuals of the Saraiki population living in different regions of Pakistan and profiles were generated using an AmpFlSTR Identifiler PCR Amplification kit. Population genetic calculations were performed on this population. Allele frequencies of the Saraiki population showed that this population is at Hardy Weinberg Equilibrium except at loci D3S1358, TH01, D13S317, TPOX and FGA, with distinct differences in HObs and HExp values. The average heterozygosity and polymorphism information content (PIC) at all loci were 0.77 and 0.766, respectively. Each STR marker showed a high degree of polymorphism and a high power of discrimination (PD). A phylogenetic tree shows that the Saraiki population living in Pakistan is genetically distinct from other geographically neighboring populations of the country. The population data presented in this study can be used as a reference database for the Saraiki population in forensic casework.